Pendidikan Kesiapsiagaan Bencana Pada Anggota Keluarga dalam Mewujudkan Keluarga Tangguh Bencana - Mahathir Mahathir; Fitra Yeni; Agus Sri Banowo; Rika Sabri (Warta Pengabdian Andalas, 2019)
Disaster is unpredictable, there is no doubt disasters cause many catastrophic losses and devastating impacts. Disaster risk reduction (DRR) is now getting spotlight attention nationally and globally. Continual and progressive efforts shall be made to prepare people from the potential hazard that threaten. Disaster preparedness is essential to be considering, it have to be prioritized by the community before the occurrence of an unexpected disaster occur. The community readiness and hardiness will lower the impact caused by the disaster. The community resilience has to be developed and make a consistent progress to achieve optimal disaster risk reduction. Family is the smallest components in the community that shall be narrowed for the direct impact in community resilience achievement. The community outreach program through family disaster preparedness education aimed to improve family resilience of disaster preparedness. Disaster preparedness education for family members delivered by using expert lecture, discussion, disaster simulation and family disaster planning. Qualitative evaluation, simulation observation and designing family planning had been conducted to all family members participated. Disaster preparedness education showed an increased of disaster preparedness basic knowledge and awareness, fulfilling any disaster query and interactive experience of simulation method. 83% family members were performed community disaster drill properly. Family disaster planning had been arranged by the family members based on the priority to fulfill in immediate time. Disaster preparedness education mark as important effort to upscale the family resilience trough disaster preparedness.